Housing practices in Malaysia and comparison with other countries / Farah Amirah Fuad, Mahazril 'Aini Yaacob and Nurul Hidayana Mohd Noor - Fuad, Farah Amirah; Yaacob, Mahazril 'Aini; Mohd Noor, Nurul Hidayana (2021)
Housing is an essential action plan for every country in the globe since it has a significant influence on the development and improvement of the economy, as well as providing a basic shelter for individuals to improve their quality of life (Bahare Fallahi, 2017; Liyana Ishak, Yakub & Achu, 2019; Osman, Ramlee, Samsudin, Rabe, Abdullah, & Khalid, 2017; Wong, Lee Chin, Seng Wong, & Chee-Lip Tee, 2019). Furthermore, housing provides a secure location, privacy, and protection that assist individuals in sustaining an economic livelihood, the risks of a changing environment, the challenges of urban crime, and governance inequities (Shaffiqa Soffian, Amelia Ahmad, & Norainah Abdul Rahman, 2018; Noraziah Wahi, Rosli Zin, Vikneswara Munikanan, Ismail Mohamad, & Syahrizan Junaini, 2018). United Nations Committee has discussed the right to adequate housing that ensures every group of people, such as women, men, youth, and children, lives in peace and dignity since the world nowadays lives in life and a health-threatening environment (Stuart Wilson, 2020). The rights upheld to recognise that a comfortable house will guarantee a better environment and a secure and productive life. Hence, these have led Malaysia and the other developing countries to implement affordable and sustainable housing policies to provide appropriate housing (Syed Jamaludin, Mahayuddin, & Hamid, 2018) and ensure that everyone, especially the lowerincome group, has access to suitable housing accommodation (Bahare Fallahi, 2017). Thus, in this paper, the researchers review housing practices in three developing countries in Asia: Malaysia, Singapore, and China. The main aim of this article is to discuss the housing practices in Malaysia with a comparison made with Singapore and China.